Association and symptom characteristics of irritable bowel syndrome among bronchial asthma patients in Kuwait - Panicker Radhakrishna; Arifhodzic Nermina; Al Ahmad Mona; Ali Seham (Annals of Thoracic Medicine, 2010)
Context : Excess prevalence of irritable bowel syndrome in asthma has been reported, suggesting a link between these two conditions. Aims: To investigate the association between irritable bowel syndrome (IBS) and asthma, and explore the symptoms of IBS among asthma patients in Kuwait. Settings and Design: Case control study. Methods: In a tertiary center, for allergy and asthma, 138 patients aged 20-65 years, with asthma, diagnosed clinically and by spirometry,were compared with 145 healthy, non-asthmatic controls matched for age, gender and nationality. Cases and controls completed a self-administered questionnaire of irritable bowel syndrome diagnosis (ROME II criteria). Statistical Analysis Used: The data were analyzed using SPSS software, and proportions were tested with Chi-square or Fisher′s test. Odds ratio (OR) with 95% Confidence Interval (CI) were calculated to identify the associated risk factors. The demographic variables were selected for logistic regression analysis. Results : A significantly large proportion (39.13%) of asthmatics had IBS as compared to 7.93% controls (P < 0.001). A higher proportion of females with IBS were observed in cases and controls (74%, 61.54%). IBS was seen in 87% cases using inhalers, and in 13% with additional oral theophylline (P < 0.001). As many as 66.6% cases, had IBS with relatively short duration of asthma (1-5 years, P < 000). Predominant symptoms of IBS in asthmatics were abdominal discomfort or distension (64.8% vs. 11.5%), (P < 0.000, OR = 14.1; 95%CI: 3.748-53.209), bloated feeling of abdomen (74.1% vs. 34.62% (P < 0.001, OR = 5.38; 95%CI:1.96-14.84)), increased frequency of stools (63%, P < 0.006). Conclusions: Irritable bowel syndrome in asthmatics was significantly high, more in the female asthmatics. Abdominal discomfort, persistent bloated feeling, increased frequency of passing stools were the most common IBS symptoms observed.